2001
DOI: 10.1037/0022-006x.69.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Screening and treatment of distress.

Abstract: The screening and treatment of psychological distress is an increasingly important aspect of providing comprehensive care to medical patients. The importance of this within oncology was illustrated most recently by the publication of the National Comprehensive Cancer Network's Distress Guidelines (Holland, 1997). Some of the conclusions drawn in a recent article by Coyne, Benazon, Gaba, Calzone, and Weber (2000), however, are in contrast to this position. Twenty-three percent of their sample reported emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Findings that women receiving results of genetic testing do have elevated distress [Lodder et al, 2001] and that women receiving services at a cancer risk evaluation are low in any interference of cancer‐specific worries in their lives [Paterson et al, 2001; Trask et al, 2001] have continued to be interpreted by investigators as indicative of the need for services. Yet it may be that the mental health issues associated with genetic testing for risk of breast and ovarian cancer are being overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Findings that women receiving results of genetic testing do have elevated distress [Lodder et al, 2001] and that women receiving services at a cancer risk evaluation are low in any interference of cancer‐specific worries in their lives [Paterson et al, 2001; Trask et al, 2001] have continued to be interpreted by investigators as indicative of the need for services. Yet it may be that the mental health issues associated with genetic testing for risk of breast and ovarian cancer are being overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment. There is currently considerable debate over how to operationalize psychobehavioral risk in medically ill patients (Benazon et al, 2002;Cavanaugh, 1995;Ketterer et al, 2002;Klinkman et al, 1998;Paterson et al, 2001;Turk & Rudy, 1988). This debate turns on old issues such as lumping versus splitting and sensitivity versus specificity.…”
Section: Triagementioning
confidence: 99%
“…Dear Editor, We are writing to respond to Paterson et al's (2001) letter concerning the Coyne, Benazon, Gaba, Calzone, and Weber (2000) study, in which we reported rates of distress and major depressive disorder (MDD) of 23% and 1%, respectively, among women enrolled in a hereditary breast and ovarian cancer registry (HBOC) and anticipating an opportunity for genetic testing. These rates are lower than what is found in primary medical care samples and argue against attributing distress or MDD among these women to their being at high risk for cancer.…”
mentioning
confidence: 99%
“…We also suggested that costly resources diverted to screening and diagnostic interviewing could better be applied to ensure informed consent and dissemination of test results to family members for whom the information could be life saving (Meijers-Heijboer et al, 2001). Paterson et al (2001) object that these conclusions run counter to recommendations that cancer patients routinely be screened for distress and that "No patient who is distressed should go untreated" (Holland, 1997, p. 114). Our sample consisted of high-risk women, about half of whom were survivors of cancer, not patients in acute cancer care.…”
mentioning
confidence: 99%
See 1 more Smart Citation